Prescriber preference for a particular tumour necrosis factor antagonist drug and treatment discontinuation: population-based cohort. Issue 9 (30th September 2014) - Fisher, Anat; Bassett, Ken; Wright, James M; Brookhart, M Alan; Freeman, Hugh J; Dormuth, Colin R
Abstract : Objective: To assess the effect of physician preference for a particular tumour necrosis factor α (TNF) antagonist on the risk of treatment discontinuation in rheumatoid arthritis. Design: Population-based cohort study. Setting: British Columbia administrative health data (inpatients, outpatients and pharmacy). Participants: 2742 British Columbia residents who initiated a first course of a TNF antagonist between 2001 and December 2008, had been diagnosed with rheumatoid arthritis, and were treated by 1 of 58 medium-volume to high-volume prescribers. Independent variable: A level of physician preference for the drug (higher or lower) was assigned based on preceding prescribing records of the care-providing physician. Higher preference was defined as at least 60% of TNF antagonist courses initiated in the preceding year. Sensitivity analysis was conducted with different thresholds for higher preference. Main outcome measure: Drug discontinuation was defined as a drug-free interval of 180 days or switching to another TNF antagonist, anakinra, rituximab or abatacept. The risk of discontinuation was compared between different levels of physician preference using survival analysis. Results: Higher preference for the prescribed TNF antagonist was associated with improved persistence with the drug (4.28 years (95% CI 3.70 to 4.90) vs 3.27 (2.84 to 3.84), with log rank test p value of 0.017). The adjusted HR for discontinuation was significantly lower in courses of drugs with higher preference (0.85 (0.76 to 0.96)). The results were robust in a sensitivity analysis. Conclusions: Higher physician preference was associated with decreased risk of discontinuing TNF antagonists in patients with rheumatoid arthritis. This finding suggests that physicians who strongly prefer a specific treatment help their patients to stay on treatment for a longer duration. Similar research on other treatments is warranted.